2016
DOI: 10.1177/0333102416648650
|View full text |Cite
|
Sign up to set email alerts
|

High leptin levels are associated with migraine with aura

Abstract: Background Migraine is a prevalent disorder characterised by recurrent headache attacks preceded or accompanied by aura in a subgroup of patients. Migraine often occurs together with major depressive disorder (MDD). Alterations of adipokine levels have been reported both in migraine and in MDD. In this cross-sectional study, we aimed to assess the associations between serum leptin and adiponectin levels and migraine or migraine subtypes. Analyses were adjusted for a lifetime history of MDD in order to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 29 publications
2
30
0
2
Order By: Relevance
“…On contrary, Pisanu et al. () showed that migraineurs had significantly higher levels of leptin than controls. Furthermore, leptin was found to be associated with the presence of migraine, concluding that this biomarker could play a role in the pathogenesis of migraine.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…On contrary, Pisanu et al. () showed that migraineurs had significantly higher levels of leptin than controls. Furthermore, leptin was found to be associated with the presence of migraine, concluding that this biomarker could play a role in the pathogenesis of migraine.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, an animal study showed that chronic administration of leptin caused changes in cortical excitability and significantly increased the occurrence of CSD, which suggests that leptin may play a role in migraine pathogenesis (Kitamura, Kanazawa, & Hamada, ). Results from studies evaluating serum leptin levels in patients with migraine are controversial (Dearborn et al., ; Guldiken, Guldiken, Demir, Turgur, & Tugrul, ; Pisanu et al., ). One study found significantly lower leptin levels in EM patients in comparison with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…These adipokines act in a similar way both in psoriasis and migraine, particularly MA. In fact, while several studies observed increased levels of Leptin in the psoriatic population, a recent work about migraine topic found hyperleptinaemia in the MA subset of patients. This is in line with the results of another study showing that hyperleptinaemia has the potential to increase cortex susceptibility to cortical spreading depression (CSD), a mechanism that is suggested to induce auras during migraine attacks we, however, did not find any relationship between BMI, presence of psoriasis and MA incidence or MA attacks.…”
Section: Discussionmentioning
confidence: 93%
“…13 Despite findings supporting relationships between migraine, particularly chronic migraine, and certain ADPs [14][15][16][17][18][19][20][21] , some discrepancies persisted in more recent studies that have evaluated the relationship between leptin, adiponectin, and migraine according to aura symptoms in their analyses. 17,19,21 From those, only one found a positive relationship between migraine with aura (MA) and leptin levels. 19 The other two studies, including a case-cohort study that included the investigation between MA symptoms and HMW adiponectin, 17 found no associations between ADPs and MA.…”
Section: Introductionmentioning
confidence: 99%
“…17,19,21 From those, only one found a positive relationship between migraine with aura (MA) and leptin levels. 19 The other two studies, including a case-cohort study that included the investigation between MA symptoms and HMW adiponectin, 17 found no associations between ADPs and MA. 17,21 As far as we know, no study has investigated the association of ADP and migraine according to aura symptoms stratified by sex in an admixture population in Latin America as the ELSA-Brasil.…”
Section: Introductionmentioning
confidence: 99%